Kepemimpinan Tri Rismaharini dalam Mengatasi Pengelolaan Sampah di Kota Surabaya - Mohd Rahmaddhoni Pratama; Fitriyah Fitriyah (Mahesa Research Center, 2021)
The city of Surabaya is becoming a global model model in the problem of tackling waste. Risma program with Sustainable Development Goals policy is able to solve the problem of waste waste in Surabaya. Furthermore, this study will explain how Tri Rismaharini's leadership as Mayor of Surabaya in driving public participation and bureaucracy in tackling the garbage problem. This research method uses descriptive skin. Research data obtained from primary data through informants surabaya city government apparatus and the community is quite representative. Secondary data by quoting books, journals, documents and online media. Data analysis techniques in this study through data reduction, data display and drawing conclusions. The results showed that Tri Rismaharini's leadership has a disciplined and assertive leadership style, both in serving the community. Although Risma is known as a leader who cannot accept criticism, nor advice. But tend to participating, because it is more concerned with the process and implementation in the field and tends to tell, where demanding to be firm and disciplined against waste management in the city of Surabaya.